The Implicit/Explicit Continuum of Life Skills Development and Transfer. Issue 4 (2nd October 2018) - Bean, Corliss; Kramers, Sara; Forneris, Tanya; Camiré, Martin
ABSTRACT: There is an ongoing discussion as to how life skills development and transfer should be addressed. Previously, researchers have proposed an implicit/explicit dichotomy to explain how life skills teaching occurs. As research within the area of sport-based youth development continues to progress, a model is needed to delineate the varying levels of implicitness/explicitness at which coaches can facilitate life skills development and transfer. Within this article, an implicit/explicit continuum of life skills development and transfer is presented and distributed across six levels: (a) structuring the sport context, (b) facilitating a positive climate, (c) discussing life skills, (d) practicing life skills, (e) discussing transfer, and (f) practicing transfer. The levels found within the continuum are grounded in existing sport psychology literature. Conceptually, researchers can use the continuum to empirically situate how coaches teach life skills. Practically, the continuum can help coaches frame their approach to life skills development and transfer.